Production and characterization of novel anti-prostate-specific antigen (PSA) monoclonal antibodies that do not detect internally cleaved Lys145-Lys146 inactive PSA. - Nurmikko, P; Väisänen, V; Piironen, T; Lindgren, S; Lilja, H; Pettersson, K (2000)
BACKGROUND: The nature of free, uncomplexed prostate-specific antigen (PSA) in the circulation is still unknown. In this study, we developed novel anti-PSA antibodies using PSA produced by a metastasized cancer cell line, LNCaP, as an immunogen. METHODS: Hybridoma cell lines were screened with different methods that aimed at finding antibodies specific for the forms of free PSA produced by LNCaP cell line. Obtained antibodies were further studied for their characteristics related to previously characterized monoclonal antibodies. RESULTS: Numerous anti-PSA antibodies were obtained, of which four represented unique epitopes previously unrecognized by us. One free-PSA-specific antibody was bound to PSA on two distinct epitopes, and one antibody was bound to the carboxyl-terminal peptide of PSA. Two antibodies were found to bind to the peptide sequence adjacent to the internal cleavage site Lys145-Lys146. These antibodies failed to recognize internally cleaved PSA at Lys145-Lys146. We could not find anti-proPSA antibodies despite the fact that LNCaP PSA contained more than one-half of the zymogen form of PSA. CONCLUSIONS: We report, for the first time, novel anti-PSA antibodies that do not recognize internally cleaved PSA at Lys145-Lys146 and thus are specific for intact, unclipped PSA.